ผลของอนุภาคไทเทเนียมไดออกไซด์ในฟิล์มไคโตซานเพื่อการกำจัดสีย้อม - ปาริชาต นรนาถตระกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This research was investigated using the chitosan film as a polymer matrix for titanium dioxide dispersion. The obtained chitosan-TiO[subscript2] composite film was utilized for treatment of dye contaminated wastewater. Chitosan-titanium dioxide composite film was prepared by solution casting, which included chitosan, TiO[subscript2], Arquad T-50 HFP as surfactant, and 1% acetic acid solution for dissolving chitosan. The solution of 1.0 g chitosan in 100 ml acetic acid was prepared, and TiO[subscript2] was subsequently added. The mixture was then casted onto an acrylic mold and allowed to air-dry. The external morphology of the composite film revealed that TiO[subscript2] was homogeneously dispersed in the film. The three types of crosslinking agent, namely glutaraldehyde, citric acid, and itaconic acid, were also studied. The effects of type and concentration of crosslinking agent was investigated and showed that chitosan film crosslinked with 1.12 mM citric acid for 5 min gave the highest tensile strength at 150.4 MPa, approximately. X-ray diffractogram patterns of the dried film revealed that the theta of crystalline region of chitosan was slightly changed. The shifting in chitosan diffractogram peak could be caused by the change of its chain orientation after the covalent bonding interaction between chitosan and crosslinking agent. The non-crosslinked chitosan- TiO[subscript2] composite film showed the highest tensile stress at maximum load with TiO[subscript2] content of 1wt%. The high content of TiO[subscript2] resulted in the poor tensile stress at maximum load due to an aggregation of TiO[subscript2]-nanoparticles. The spent film for dye removal had a lower tensile stress at maximum load compared to that of the original film. Three reactive dyes, RR 120, RY 17, and RB 220, were used as representative contaminants. The optimal TiO[subscript2] loaded in chitosan films was 1 wt% of chitosan for dye removal in both UV and dark conditions. The non-crosslinked chitosan- TiO[subscript2] composite film showed the higher efficiency in dye removal than those of the crosslinked film. Dye removal under UV light source had the higher efficiency than through the dark for all initial dyes concentrations in the range of 10 to 100 mg/L. The average percent ratio of sorption to photocatalysis of RR 120, RY 17, and RB 220 were 70.7:29.3, 78.5:21.5, and 92.2:7.8, respectively. The Langmuir isotherm was used for data analysis in the dark condition showed that a calculated maximum sorption capacity (q[subscriptm)] of RR 120, R 17, and RB 220 were 46.8, 427.1, and 229.1 mg-dye/g-chitosan- TiO[subscript2] film, respectively. The analysis of dye removal in the UV condition by Langmuir-Hinshelwood model showed that the dye removal efficiency was less than the experimental results. This indicated that photocatalysis process occurred on the TiO[subscript2] surface and in the solution. In addition, the sorption mechanism of dye on film surface resulted in the under estimated of the model. The optimal pH in dye removal for RR 120 and RY 17 were prioritized from high to low as 9>7>4, while the RB 220 was ordered 7>4>9.